Volar Plating: Imaging Modalities for the Detection of Screw Penetration - Bergsma, Minke; Denk, Katharina; Doornberg, Job N.; van den Bekerom, Michel P. J.; Kerkhoffs, Gino M. M. J.; Jaarsma, Ruurd L.; Obdeijn, Miryam C. (Journal of Wrist Surgery, 2019)
Background Volar plating for distal radius fractures exposes the risk of extensor tendon rupture, mechanical problems, and osteoarthritis due to protruding screws.Purposes The purpose of this review was to identify the best intraoperative diagnostic imaging modality to identify dorsal and intra-articular protruding screws in volar plating for distal radius fractures.Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were followed for this review. In vitro and in vivo studies that analyzed the reliability, efficacy, and/or accuracy of intraoperatively available imaging modalities for the detection of dorsal or intra-articular screw protrusion after volar plating for distal radius fractures were included.Results Described additional imaging modalities are additional fluoroscopic views (pronated views, dorsal tangential view [DTV], radial groove view [RGV], and carpal shoot through [CST] view), three-dimensional (3D) and rotational fluoroscopies, and ultrasound (US). For detection of dorsal screw penetration, additional fluoroscopic views show better results than conventional views. Based on small (pilot) studies, US seems to be promising. For intra-articular screw placement, 3D or 360 degrees fluoroscopy shows better result than conventional views.Conclusion Based on this systematic review, the authors recommend the use of at least one of the following additional imaging modalities to prevent dorsal protruding screws: CST view, DTV, or RGV. Tilt views are recommended for intra-articular assessment. Of all additional fluoroscopic views, the DTV is most studied and proves to be practical and time efficient, with higher efficacy, accuracy, and reliability compared with conventional views.Level of Evidence The level of evidence is Level III.
Keywords: distal radius fracture; volar plate; screw penetration; dorsal; intra-articular